Molecular dynamics study of the effect of calcium ions on the thermostability of Bacillus Amyloliquefaciens Phytase - Ibrahim Ali , Noorbatcha; Sultan, A. M.; Amid, Azura; Hamzah, Mohd. Salleh (INSI Publications, 2012)
Phytase is added to animal feeds to improve phosphorus absorption and reduce phosphorus excretion of swine and poultry. It hydrolyses phytate, which is a major form of storage of cereal grains and legumes in commercial animal feeds, into myo-inositol and inorganic phosphate. Adequate thermostability of phytase is necessary for field application as diets for swine and poultry are normally pelleted at high temperatures (60-80°C). In this study, Molecular Dynamics simulation (MD) was used to study the effect of calcium metal ions on the thermostability of Bacillus amyloliquefacience phytase. MD simulations of the enzyme in the calcium-loaded and calcium-free states were performed at 60°C (333 K) and 80°C (353 K) in water as the solvent medium, for duration of 4 ns. Root mean square deviations (RMSD) of calcium-bound residues, backbone atoms, and other secondary structures were found to be lower in the presence of calcium ions at both temperatures. In addition, calcium-loaded enzyme was found to have fewer numbers of hydrogen bonds and salt bridges at both temperatures, yet calcium-loaded enzyme remains more thermostable due to network of electrostatic interactions induced by calcium binding. The binding effect of calcium ions becomes weaker at 80°C and the small increase of binding effect offered by the calcium ions at higher temperatures in not sufficient enough to maintain the activity at this temperature. It is proposed that suitable mutations at the coil region would lead to increase in the stability of the enzyme at high temperatures.